Selective Synthesis of Bismuth Nanoflower by L-Aspartic Acid Assisted Hydrothermal Method - Xie, Jinsong; Guan, Yucheng; Tian, Changan; Lu, Hongdian; Han, Chengliang; Yin, Qiyi; Zhao, Difang; Ding, Ming (Asian Journal of Chemistry, 2014)
In this paper, three dimensional (3D) flower-like bismuth nanostructures constructed by nanorods were synthesized by a hydrothermal method, using L-aspartic acid and bismuth nitrate as raw materials and deionized water as solvent. The morphologies, structures of as-prepared products were tested by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, respectively. The optimized reaction time, ratio of reactants and the pH value of the solution were given by different experimental conditions. The effects of reaction conditions on the morphologies of the products were investigated and the formed mechanism was also premilarily discussed.